The Effectiveness of Using Media Technology in Islamic Religious Education in an Independent Curriculum: Technocultural Study of Religious Education - Suraijiah; Rusdiana; Rusdiah; M. Ramli; Murdan (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
The study aimed to assess the impact of media technology on the teaching and learning process of Islamic religious education within an independent curriculum. Through interviews, observations, and document analysis, the study found that integrating media technology positively influenced the teaching and learning experience. Multimedia presentations, educational websites, and digital applications enhanced students' engagement, motivation, and understanding of Islamic principles and teachings. Interactive and collaborative learning was facilitated, allowing students to participate actively in discussions and group activities. Media technology also provided opportunities for personalized learning, allowing students to explore Islamic concepts at their own pace and according to their learning styles. It fostered creativity and critical thinking skills by encouraging students to analyze and interpret religious texts through interactive media platforms. However, challenges such as limited access to technology resources, technical difficulties, and concerns about content authenticity were identified. The study emphasized the need for appropriate teacher training and support to integrate media technology into the curriculum effectively. In conclusion, the study demonstrated the effectiveness of media technology in Islamic Religious Education within an independent curriculum. It was integrating media tools enhanced engagement, motivation, and understanding among students while enabling interactive and personalized learning experiences. Addressing resources, technical issues, and content reliability challenges is essential for successful implementation. Keywords: Media Technology, Independent Curriculum, Interactive Learning